John G. Aikin, A Digest of the Laws of the State of Alabama 391–92, § 7 (1833) - (:unkn) unknown (My University, 1833)
Prohibited any slave from keeping or carrying any gun or ammunition without permission from a justice of the peace.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES